Biografia e história: panteonização e iconoclastia em narrativas de Raimundo Magalhães Junior - Muniz Junior, João [UNESP] (2015)
This research aimsto analyze the aspects of biographical worksby Raimundo Magalhães Junior. Therefore, we proposedto perform this study by using the biographies: Deodoro, a espada contra oImpério(1957); Rui, o homem e o mito(1964); and A vida turbulenta de José do Patrocínio(1969),in order to analyze history writing in biographical narratives written by Raimundo Magalhães Junior. This author's biographical text is considered rich regarding the issues it raises for one to reflect on the hybrid constitution of gender, part history, part literature, which aims -through the narrative of lives -to constructa historical awareness related to a historiographical perspective. The study of hisbiographism is an opportunity to discuss the biographical genre and its relationship to literary narrative and historywriting. Furthermore, we can question the temporality and notion of history shared by the text, as well as his biographical method, and how the findings in archives research are used. It's worth noticing that such issues have not been sufficiently explored, neither has the biographical worksby Raimundo Magalhães Junior